India House - Nayar, Kuldip (New Delhi, 1992)
The six months that the author, one of India's most respected journalists, spent as India's High Commissioner to the UK were a time of much gains in Indo-UK co-operation. Nayar eased visa restrictions, sought to redress the grievances of Indians in Britain, had fruitful talks with Margaret Thatcher and so on. This book is an account of his time as a diplomat.
Keywords: Ambassadors India Biography 1990